Análisis del Comportamiento de las Importaciones de la Carga Rodada en el Puerto de Santa Marta, Conforme a la Dinámica de la Cadena De Suministro, Tomando Como Referencia los Años 2016 al 2021. (2022)
The general objective of this research is to analyze the behavior of imports of ro-ro cargo in the port of Santa Marta, according to the dynamics of the supply chain, taking the years 2016 to 2021 as a reference. To develop it, a data review was carried out. And information through secondary sources, aligned with a quantitative analytical study. The result of these inquiries led to the construction of some activities to achieve the purpose of the monograph, within which we have the identification of each of the activities, their purpose and those responsible for the ro-ro supply chain. By virtue of this, make a recount of the last five years of the processes executed in the port to show its growth and the technologies implemented in order to become the leader at the national level. Similarly, set management indicators to control and measure each of the supply chain processes to take corrective and preventive actions, reduce errors, eliminate changes, attract customers, among others.